1999
DOI: 10.1051/lait:1999110
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification and characterization of the bacteriocin produced by Propionibacterium jensenii B1264

Abstract: -Thirteen dairy propionibacteria were screened for catalase-insensitive, protease-sensitive inhibition of various Gram-positive and Gram-negative bacteria. Production of bacteriocin-like agents was identified in 8 ofthese cultures. The bacteriocin produced by Propionibacteriumjensenii B 1264 inhibited closely related propionibacteria and lactic acid bacteria and was bactericidal to Lactobacillus delbrueckii subsp. lactis ATCC 4797. It was produced in sodium lactate broth cultures during stationary phase; maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 16 publications
(18 reference statements)
2
22
0
Order By: Relevance
“…Ratman et al [33] also reported that extracellular bacteriocin could only be detected in the late stationary phase of P. jensenii B1264. These researchers suggested that cell lysis occurred and that the bacteriocin was released during lysis.…”
Section: Production In Liquid Mediamentioning
confidence: 97%
See 3 more Smart Citations
“…Ratman et al [33] also reported that extracellular bacteriocin could only be detected in the late stationary phase of P. jensenii B1264. These researchers suggested that cell lysis occurred and that the bacteriocin was released during lysis.…”
Section: Production In Liquid Mediamentioning
confidence: 97%
“…In a later screening this strain along with other lactobacilli and PAB were used as indicators [33]. Eight of the thirteen strains tested positive against at least one indicator, but three of them were only active against lactobacilli.…”
Section: Screening For Bacteriocin Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Among them it could be mentioned: Propionicin PLG-1 and GBZ-1 produced by P. thoenii 127 [81]; Jenseniin G isolated from P. thoenii P126 [82]; Propionicins SM1 and SM2 produced by P. jensenii DF1 [83]; Propionicin T1 synthesized by P. thoenii 419 and LMG2792 [84]; Thoenicin 447 isolated from P. thoenii 447 [85]; Acnecin produced by a strain of P. acnes [86] and several other propionicins [87][88][89].…”
Section: Antimicrobials Production: Propionic Acid and Bacteriocinsmentioning
confidence: 99%